An Antibody-based Multifaceted Approach Targeting the Human Transferrin Receptor for the Treatment of B-cell Malignancies - Daniels, Tracy R. (2011)
We previously developed an antibody-avidin fusion protein (ch128.1Av) targeting the human transferrin receptor 1 (TfR1, also known as CD71), which demonstrates direct in vitro cytotoxicity against malignant hematopoietic cells. This cytotoxicity is attributed to its ability to decrease the level of TfR1 leading to lethal iron deprivation. We now report that ch128.1Av shows the ability to bind the Fc γ receptors and the complement component C1q, suggesting that it is capable of eliciting Fcmediated effector functions such as antibody-dependent cellmediated cytotoxicity and complement-mediated cytotoxicity. In addition, in 2 disseminated multiple myeloma xenograft mouse models, we show that a single dose of ch128.1Av results in significant antitumor activity, including long-term survival. It is interesting to note that the parental antibody without avidin (ch128.1) also shows remarkable in vivo anticancer activity despite its limited in vitro cytotoxicity. Finally, we demonstrate that ch128.1Av is not toxic to pluripotent hematopoietic progenitor cells using the long-term cell-initiating culture assay suggesting that these important progenitors would be preserved in different therapeutic approaches, including the in vitro purging of cancer cells for autologous transplantation and in vivo passive immunotherapy. Our results suggest that ch128.1Av and ch128.1 may be effective in the therapy of human multiple myeloma and potentially other hematopoietic malignancies.